Lock-Out Valve to Decrease Catheter-Associated Urinary Tract Infections - Amir Shbeeb; Jennifer L. Young; Scott A. Hart; Juliet C. Hart; Joel Gelman (Advances in Urology)
Patients with long-term indwelling urinary catheters are at an increased risk for urinary tract infection due to bacteriuria. Catheter-associated urinary tract infections (CAUTIs) are a significant source of morbidity and mortality in long-term care facilities as well as in ambulatory patients requiring long-term catheterization. There is increased interest in the financial impact of CAUTI as Medicare no longer provides reimbursement for nosocomial CAUTIs. Ascending bacteria may in part enter the closed drainage system when the patient switches between leg and night collection bags. In an attempt to reduce this ascent, a double valve lock-out system was devised that maintains a closed system during bag exchange. The concept is introduced and CAUTIs are reviewed.